Power distance in online learning: Experience of Chinese learners in U.S. higher education - Yi (Leaf) Zhang (Athabasca University Press, 2013)
The purpose of this research study was to explore the influence of Confucian-heritage culture on Chinese learners’ online learning and engagement in online discussion in U.S. higher education. More specifically, this research studied Chinese learners’ perceptions of power distance and its impact on their interactions with instructors and peers in an online setting. This study was conducted at a research university in the southwestern U.S. Twelve undergraduate students from the Confucian-heritage culture, including mainland China, Taiwan, and Hong Kong, participated in the study. This study provided evidence that the online setting benefited these Chinese learners’ engagement in class discussion, but it may increase the level of anxiety in their participation. Learning, perceived by the Chinese learners, was more instructor-centered. Instructors were viewed as authorities, major sources of knowledge, and possessed high power to students. As a result, when encountering difficulties in learning, the Chinese learners were intimidated to interact with their instructors. Instead, they tended to seek help from peers, particularly those who shared similar cultural and linguistic backgrounds.